Prolactin levels in drug-naïve first episode nonaffective psychosis patients compared with healthy controls. Sex differences. (June 2019) - Del Cacho, N.; Butjosa, A.; Vila-Badia, R.; Cuadras, D.; Kaplan, M.; Rubio-Abadal, E.; Pardo, M.; Muñoz-Samons, D.; Cuevas-Esteban, J.; Saenz- Navarrete, G.; Usall, J.; ,
Highlights: First episode drug-naïve psychotic patients had significantly elevated prolactin levels compared to healthy controls. Significant differences in prolactin levels between men and women were not observed in patients or controls. These results suggest that treatment with antipsychotic medications that do not elevate prolactin may be worth considering for first episode patients with elevated premedication prolactin levels, as suggested by previous authors. Abstract: Recent studies have found hyperprolactinemia in first episode psychotic patients that had not previously received antipsychotic treatment (drug-naïve). Our goal was to learn whether there were differences in baseline prolactin concentrations between drug-naïve psychotic patients and healthy controls, as well as to study possible gender differences in the prolactin elevation. A cross-sectional study was conducted that included 61 drug-naïve psychosis patients and 45 healthy controls (aged between 14-55 years old). A blood sample was extracted between 8 and 10 a.m. Prolactin levels and TSH were determined. The Perceived Stress Scale (PSS) was conducted across the sample. This study showed significantly higher levels of prolactin in drug-naïve patients compared to healthy controls. These results were maintained after controlling prolactin levels for sex, age, THC consumption, baseline TSH, and PSS. A significant correlation between prolactin and PSS was not observed. Significant differences in prolactin levels between men and women were not observed. These results are clinically important because if elevated baseline prolactin levels are detected in these patients, it will be necessary to initiate neuroleptics that do not increase this hormone. There was no evidence that stress was related to an increase in prolactin at the onset of psychosis.